1975
DOI: 10.1111/j.1440-1681.1975.tb03028.x
|View full text |Cite
|
Sign up to set email alerts
|

Human cardiorespiratory responses to acute cold exposure

Abstract: 1. Respiratory and circulatory functions of minimally clad human subjects were studied before and during acute exposure to ambient temperatures of 4.5-6.5 degrees C. 2. After 1 h of cold exposure, subjects showed increases of ventilation, O2 UPTAKE AND CARDIAC OUTPUT. Rectal temperatures fell. 3. During exercise in the cold conditions, oxygen uptake and cardiac output were greater than during the same exercise at normal temperature. 4. The increased cardiac output during cold exposure was achieved by an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…A reduction in exercise economy/efficiency may be partly responsible for a decline in aerobic performance in cold environments. Multiple studies have shown that running at the same speed or cycling at the same external workload elicits a higher VO 2 in the cold, compared to temperate or hot environments (44,47,94,117,175,176,186,205), although this is not universal (135,198,204). In the studies cited earlier that showed differences, this reduction in economy/efficiency occurred even though deep body temperature, well known to increase VO 2 , was not lower among the different ambient temperatures studied.…”
Section: Metabolismmentioning
confidence: 57%
“…A reduction in exercise economy/efficiency may be partly responsible for a decline in aerobic performance in cold environments. Multiple studies have shown that running at the same speed or cycling at the same external workload elicits a higher VO 2 in the cold, compared to temperate or hot environments (44,47,94,117,175,176,186,205), although this is not universal (135,198,204). In the studies cited earlier that showed differences, this reduction in economy/efficiency occurred even though deep body temperature, well known to increase VO 2 , was not lower among the different ambient temperatures studied.…”
Section: Metabolismmentioning
confidence: 57%
“…During the 19°C trial, however, the magnitude of CV drift was greater than that demonstrated in the 0°C trial, with significantly greater HR for a considerable period of the 19°C trial. During the 0°C trial, a peripheral vasoconstriction, stimulated in an effort to conserve heat, may have led to the maintenance of central blood volume during exercise (8). Additionally, during the 0°C trial, it is likely that the rate of fluid loss through sweat production was diminished in comparison with the 19°C trial as evidenced by the greater loss of body mass during the 19°C trial (2.3% vs 1.1%).…”
Section: Discussionmentioning
confidence: 80%
“…This suggests an increase in both cardiac output and peripheral resistance which has been shown to occur in healthy volunteers both during acute (Keatinge et al, 1964) and long-term exposure to cold (Hanna et al, 1975). In patients with angina pectoris, and in healthy controls, cold has been found to increase peripheral resistance and blood pressure at rest (Neill et al, 1974).…”
Section: Discussionmentioning
confidence: 91%